The diagnostic value of two commercially available human cTnI assays in goat kids with myocarditis - Karapinar, Tolga; Eroksuz, Yesari; Hayirli, Armagan; Beytut, Enver; Kaynar, Ozgur; Baydar, Ersoy; Isidan, Hakan (Wiley, 2016)
BackgroundCardiac troponin I (cTnI) is a peripheral blood marker for myocardial damage. Because of the unavailability of goat-specific cTnI assays human cTnI assays may be validated for detection of myocarditis in goat kids. ObjectivesThe purpose of the study was to evaluate 2 commercially available human cTnI assays in goat kids with myocardial damage, and to determine the cTnI expression in cardiac muscle. Materials and MethodsPlasma cTnI concentrations were measured in healthy goat kids (n = 7) and goat kids with myocardial damage (n = 8) using the Beckman Coulter Access Accu TnI and the Biomerieux Vidas Ultra. The results were correlated with gross necropsy and histopathologic findings, and cTnI immunhistochemistry in cardiac tissue. ResultsMacro- and microscopic findings confirmed myocardial damage in the myocarditis group. Mean plasma cTnI concentration was significantly higher in the myocarditis group than in the healthy control group (104.82 vs 0.02 ng/mL). The overall mean plasma cTnI concentration measured by Biomerieux Vidas Ultra (61.75 ng/mL, 95% CI: 19.55-103.95) was comparable to the mean measured by Beckman Coulter Access Accu TnI (50.08 ng/mL, 95% CI: 24.11-76.06), and cTnI concentrations measured by these assays were highly correlated (r = .977) with a -6.2% bias. Both assays were precise and accurate. ConclusionThe human-specific Beckman Coulter Access Accu TnI and the Biomerieux Vidas Ultra can be used for diagnostic confirmation of myocardial damage in caprine medicine.
Keywords: Biomarker; cTnI; goat; myocardial damage